Penerapan Sanksi bagi Pelaku Tindak Pidana Pencurian Menurut Hukum Pidana Adat Minangkabau Ditinjau dari Hukum Pidana Positif - Alyusnan Yusuf; Edi Setiadi (UNISBA Press, 2023)
Abstract. The application of sanctions in the Minangkabau customary law itself, especially the crime of theft, has existed for a long time, although there are no rules that regulate it beforehand. Furthermore, in customary settlements, there are no social differences in imposing sanctions. In addition to the sanctions that have been regulated in the material sanctions, customary law has moral sanctions that are borne by the perpetrator and his family and for life. The position of customary criminal law in Indonesian criminal law policies deserves to be considered, because the existence of customary criminal law in the legal system in Indonesia is recognized in several laws and regulations, court decisions, so that the location of customary criminal law in the formation of national criminal law is a source for national law. Then in the 2008 RKUHP the position of customary criminal law is used not only as a source of criminal law, but also as a source of material legality of criminal law as stated in the provisions of Article 1 paragraph (3), (4) of the 2008 RKUHP, the source of material legality as a counterbalance to the principle of formal legality as regulated in article 1 paragraph (1) of the 2008 RKUHP. Abstrak. Penerapan sanksi dalam pidana adat Minangkabau sendiri khusunya pidana pencurian sudah ada sejak dulu, walaupun tidak ada aturan yang mengatur sebelumnya. Selanjutnya dalam penyelesaian adat tidak ada perbedaan sosial dalam menjatuhkan sanksi,Selain sanksi yang sudah diatur dalam yaitu sanksi material, hukum adat mempunyai sanksi moral yang ditanggung pelaku dan keluarganya dan seumur hidup. Kedudukan hukum pidana adat dalam kebijakan hukum pidana Indonesia patut untuk dipertimbangkan, dikarenakan keberadaan hukum pidana adat dalam sistem hukum di Indonesia diakui dalam beberapa peraturan perundang-undangan, putusan Pengadilan, sehingga letak hukum pidana adat dalam pembentukan hukum pidana nasional adalah sebagai sumber untuk hukum nasional. Kemudian dalam RKUHP Tahun 2008 kedudukan hukum pidana adat digunakan bukan saja sebagai sumber hukum pidana, tetapi juga sebagai sumber legalitas materiil hukum pidana sebagaimana tertuang dalam ketentuan pasal 1 ayat (3), (4) RKUHP Tahun 2008, sumber legalitas materiil tersebut sebagai penyeimbang asas legalitas formal yang diatur dalam pasal 1 ayat (1) RKUHP Tahun 2008.